Titerphilia - The Irresistible Urge to Measure Postimmunization Antibody Values. Issue 6 (6th May 2022) - Heininger, Ulrich; Plotkin, Stanley
Abstract : Some physicians and parents request to measure antimeasles serum IgG antibodies after measles-mumps-rubella (MMR) vaccination. Often, vaccine skeptical parents want to know if their child is "immune" after the first dose to avoid the second dose. In the usual healthy child, this should be discouraged for the following reasons. Commercially available antibody assays do not measure functional (neutralizing) antibodies. They cannot reliably measure immunity against measles and were designed to measure naturally acquired antibodies rather than those induced by vaccination. Furthermore, MMR also includes mumps and rubella vaccine viruses, which also require 2 doses for optimal protection; there is no reliable serologic correlate of protection for mumps. Therefore, the 2-dose MMR immunization concept is by far more effective, efficient and reliable than a single dose strategy based on a post-dose 1 positive anti-measles-IgG test. Consequently, physicians should resist the desire to measure antimeasles IgG antibodies unless there is a clear indication (e.g., immunodeficiency) or official recommendation as part of the national immunization program.